Prepartum and/or postpartum supplementation with low-moisture molasses blocks to optimize fertility and calf performance in primiparous beef cows - Catussi, Bruna Lima Chechin (2021)
Nutritional management of the herd is a determining factor for the production system in beef cattle, as the nutritional and metabolic state of the animal directly affects their reproductive functions. In order to study supplementation strategies, 417 pregnant Nelore heifers were used to evaluate the effects of block supplementation (offered weekly) during pre (90 days before calving: D-90) and/or postpartum (120 days after calving) on reproductive and progeny performance. Heifers were randomly allocated in four experimental groups: 1) Group CC: heifers received mineral supplement in loose meal form (0.06% of BW) offered daily (control supplementation; C) before and after parturition (n= 108); 2) Group CB: received C before parturition and mineral protein supplement in block form (0.07% of BW) offered weekly (block supplementation; B) after parturition (n= 117); 3) Group BC: received B before and C after parturition (n= 103) and 4) Group BB: received B before and B after parturition (n= 89). During pre and postpartum periods, the performance [body weight (BW); body condition score (BCS); subcutaneous backfat thickness (BFAT); rump fat thickness (RFAT), and calf body weight (CW)] were evaluated. Blood samples were collected on a subset of animals (n= 120) at D-90, D40 and D80 for metabolites and hormonal analysis (D0= parturition). All animals were synchronized for FTAI using estradiol/progesterone-based protocol at D40 and D80 (non-pregnant at 1st FTAI). Pregnancy diagnosis was performed 30 days after FTAI and 30 days after the end of the breeding season (BS). All data was analyzed by orthogonal contrasts [C1: Control vs. block supplementation (CC vs. BB+ BC+ CB); C2: B in both periods (pre and postpartum) vs. B in one of the periods (pre or postpartum; BB vs. BC+ CB); C3: B only during prepartum vs. B only during postpartum (BC vs. CB). Block supplementation (C1) increased pregnancy at first FTAI (P= 0.04) and overall pregnancy rate (P= 0.05). There was interaction time*treatment for BW (P< 0.0001) and BCS (P> 0.0001). Supplemented cows had greater BCS only at parturition (D0; P= 0.04)) and at D40 (P= 0.02) and greater BW only at D40. Also, supplemented cows had greater BFAT (P= 0.03) and RFAT (P= 0.03) at D40. There was interaction time*treatment for glucose concentrations (P= 0.0002), which were higher for supplemented cows only at D40 (P= 0.01). Insulin concentrations were higher for supplemented cows (P= 0.008). Furthermore, Time*treatment interaction for CW (P< 0.0001) was observed. CW was superior for calves born by supplemented cows at 80 and 120 days old (P≤0.03), but not at D170 (P= 0.55) and at weaning (P= 0.38). Although no differences in reproductive performance in C2 (P> 0.15), the CW was higher for calves born by cows supplemented before and after parturition at 80 (P< 0.001), 120 (P< 0.001), 170 (P= 0.002) and 210 (P= 0.02) days old. No reproductive differences were observed in C3 (P> 0.8). Nevertheless, BCS at parturition was greater for cows supplemented only during prepartum (P< 0.001). Furthermore, BCS at D170 was greater for cows supplemented only during postpartum (P= 0.001). Calves born by supplemented cows only during postpartum were heavier only at 120 days old (P= 0.002). In summary, regardless of period of treatment, block supplementation increased pregnancy at first FTAI and overall pregnancy rate. Additionality, block supplementation during both pre and postpartum periods improved progeny weight gain until weaning. Block supplementation can be a tool to optimize fertility and calf performance in Nelore primiparous cows.